The impacts of the use of portfolio on EFL learners’ writing performance : - Nguyễn, Anh Tài (Trường Đại học Cần Thơ, 2015)
Investigated the impacts of the use of portfolio on learners writing performance in terms of paragraph components such as content, organization, vocabulary, language and mechanics as well as the learners' attitudes toward of the use of portfolio in the writing learning process